PENERAPAN E-GOVERNMENT DALAM MEWUJUDKAN TRANSPARANSI TATA KELOLA PEMERINTAHAN DESA (Studi pada Pemerintahan Desa Bulo Timoreng) - Anggun Pertiwi; Herman Dema; Ahmad Mustanir; Eka Anugrah (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
This study aims to analyze the Application of E-Government in Realizing Transparency in Village Governance in Bulo Timoreng Village. This research use desciptive qualitative approach. The results show that e-government in transparency uses an implementation system. The implementation is by coordinating with the community to find out the problems or benefits that arise in the Implementation of E-Government in Realizing Transparency in Village Governance in Bulo Timoreng Village.